Desulfurization of fuel using ionic liquids: Computational selection of cation and anion - Salleh, M.Z.M. (Trans Tech Publications Ltd, 2014)
Selection of potential ionic liquid (IL) is carried out in this work using COSMO-RS by analyzing the interaction between dibenzothiophene (DBT) and IL in dodecane. Sigma profile, capacity and selectivity at infinite dilution were used to predict the suitable ILs in desulfurization. Result shows that increasing alkyl length and incorporating nitrile group will increase the capacity and selectivity respectively. 1-butyl-6-methylquinolonium C4mquin+, 1-butyl-3- methylimidazolium Bmim+, thiocyanate SCN- and dicyanamide N(CN)2- are potentially good cations and anions. Â© 2014 Trans Tech Publications, Switzerland.